Stratification by MYC expression has prognostic impact in MYC translocated B‐cell lymphoma—Identifies a subgroup of patients with poor outcome. (6th March 2019) - Pedersen, Mette Ølgod; Gang, Anne Ortved; Clasen‐Linde, Erik; Breinholt, Marie Fredslund; Knudsen, Helle; Nielsen, Signe Ledou; Poulsen, Tim Svenstrup; Klausen, Tobias Wirenfeldt; Høgdall, Estrid; Nørgaard, Peter
Abstract: Objective: In patients with large B‐cell lymphoma (LBCL) according to WHO, the prognostic significance of MYC translocation is still not sufficiently clarified. We therefore aimed to investigate whether prognostication could be improved in patients with MYC translocation positive LBCL by additional stratification according to MYC and BCL2 protein expression levels or MYC translocation partner gene as well as concurrent BCL2 and/or BCL6 translocation (DH). Methods: From an unselected consecutive cohort of >600 patients with LBCL investigated with fluorescent in situ hybridization (FISH), 64 patients were diagnosed with MYC translocation positive LBCL and included in the study. They were further investigated for supplemental translocations with FISH and MYC and BCL2 protein expression with immunohistochemistry (IHC). Results: MYC expression >75% was associated with both reduced progression‐free survival (PFS) and overall survival (OS) (PFS: HR 6.8 (95% CI 1.5‐31), P  = 0.004. OS: HR 4.3 (95% CI 0.9‐21), P  = 0.05). Immunoglobulin ( IG ) MYC translocation partner gene was related to high MYC protein expression ( P  = 0.047) but was not prognostic for PFS ( P  = 0.8) or OS ( P  = 0.6). DH did not confer a worse outcome compared to MYC single hit (SH). These findings were confirmed in a comparable, independent validation cohort of 28 patients with MYC translocation positive LBCL. All patients included in the survival analyses were treated with R‐CHOP (rituximab, cyclophosphamide, doxorubicin, vincristine, and prednisone) or R‐CHOEP (R‐CHOP + etoposide). Conclusion: These findings suggest that in patients with LBCL stratification by MYC protein expression level significantly improves the prognostic impact associated with MYC translocation.